Life‐history costs associated with resistance to lambda‐cyhalothrin in the predatory ladybird beetle Eriopis connexa. (29th October 2012) - Ferreira, Emerson S.; Rodrigues, Agna R. S.; Silva‐Torres, Christian S. A.; Torres, Jorge B.
<x xml:space="preserve">Abstract</x> 1 The present study assessed the fitness of a lambda‐cyhalothrin‐resistant population of Eriopis connexa (Germar) with respect to development, reproduction, survival under prey scarcity and prey consumption. 2 Nontreated resistant females (R0) and females recovered after the topical application of 0.05, 0.10 and 0.25 mg active ingredient/mL of lambda‐cyhalothrin (R0.05, R0.10 and R0.25) produced, on average, 50% less eggs than susceptible females (S0), irrespective of the applied dose. All of the other traits evaluated remained similar. With respect to developmental characteristics, the larval viability and weight of adult male R0.25 progeny were statistically lower compared with the R0 and S0 progenies. Prey scarcity between days 3 and 13 of adulthood did not affect R0 and R0.25 survival, although egg production was significantly lower for R0 females, followed by R0.25 females, compared with S0 females. 3 The mean consumption of cotton aphids Aphis gossypii Glover over 5 consecutive days was significantly higher for S0, followed by R0 and R0.25, up to day 3 of observation. However, after day 4, prey consumption was similar among the three populations. 4 The results obtained in the present study show that resistant females have a lower reproductive output than susceptible females and that this is not related to the knockdown effect; however, the costs of recovering from knockdown interfere with the survival of offspring and also slightly with prey consumption. Thus, we conclude that the lambda‐cyhalothrin‐resistant E. connexa population exhibits an egg production disadvantage relative to the susceptible population and that this is increased when the population is subjected to prey scarcity.